2018
DOI: 10.1364/boe.9.003983
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study on the detection of early dental caries using thermo-photonic lock-in imaging and optical coherence tomography

Abstract: Early detection of dental caries is known to be the key to the effectiveness of therapeutic and preventive approaches in dentistry. However, existing clinical detection techniques, such as radiographs, are not sufficiently sensitive to detect and monitor the progression of caries at early stages. As such, in recent years, several optics-based imaging modalities have been proposed for the early detection of caries. The majority of these techniques rely on the enhancement of light scattering in early carious les… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 32 publications
1
15
0
Order By: Relevance
“…In these images, the defective area (hole) can be realized in amplitude images as a region of higher amplitude, confirming additional diffusive contributions of thermal energy to sample surface as a result of the introduction of thermal impedance by the defect. These observations are consistent with those obtained in our previous benchmark tests using expensive research-grade IR cameras 7,30,31 . While defects can be detected in all 3 frame rates, the defect contrast, and consequently reliability of defect detection, is directly correlated with an increase in the frame rate.…”
Section: Resultssupporting
confidence: 92%
“…In these images, the defective area (hole) can be realized in amplitude images as a region of higher amplitude, confirming additional diffusive contributions of thermal energy to sample surface as a result of the introduction of thermal impedance by the defect. These observations are consistent with those obtained in our previous benchmark tests using expensive research-grade IR cameras 7,30,31 . While defects can be detected in all 3 frame rates, the defect contrast, and consequently reliability of defect detection, is directly correlated with an increase in the frame rate.…”
Section: Resultssupporting
confidence: 92%
“…Similar to ultrasound imaging, OCT utilizes an interferometer to acquire a depth-dependent backscattered signal from the sample to retrieve its depth-resolved structure 10 . Previous studies have successfully demonstrated that OCT may be used for various biomedical applications, such as, ophthalmology 11,12 , dermatology 13,14 , cardiology 15,16 , and tooth evaluation 17,18 . It was found that OCT could serve as a potential diagnostic tool for caries, cracks, and tooth defects 1922 .…”
Section: Introductionmentioning
confidence: 99%
“…As well, swept-source cross polarized (CP)-OCT at 1310 nm has recently been employed to generate 3D tomographic images of teeth with occlusal lesions 23 . However, a recent comparison of 1310 nm (CP)-OCT and 808 nm thermophonic lock-in (TPLI) imaging (in the 8–14 μm spectral range) has shown superior sensitivity and detection threshold for the thermophotonics-based method in early caries detection 24 . Furthermore, OCT penetration depth, particularly in the λ < 1,000 nm range (~1.3 mm at 840 nm 25 ), is limited by the purely optical nature of the method, which solely depends on photon penetration.…”
Section: Introductionmentioning
confidence: 99%